Effectiveness of Early Screening for Postpartum Depression Among Mothers with a History of Depression - Lestari Nutari; Sryade Nur Safitri (International Journal of Nursing and Midwifery Research, 2026)
Postpartum Depression is a common mental health condition that affects many women after childbirth and can significantly impact maternal well-being, infant development, and family functioning. Despite its potential consequences, postpartum depression is often underdiagnosed due to the absence of systematic mental health screening in many maternal healthcare services. Early screening is therefore essential to detect depressive symptoms at an early stage and provide appropriate psychological support and intervention. This study aimed to evaluate the effectiveness of early screening in detecting postpartum depression among mothers with a history of depression. This research employed a quantitative cross-sectional design. The participants consisted of postpartum mothers with a documented history of depression who attended postnatal care services in hospitals, maternal health clinics, and community health centers. Data were collected using standardized screening instruments, including the Edinburgh Postnatal Depression Scale and the Patient Health Questionnaire-9. Descriptive statistics were used to summarize participant characteristics and the prevalence of depressive symptoms, while inferential analyses, including chi-square tests and logistic regression, were conducted to examine the relationship between screening results and potential risk factors. The findings showed that approximately 28.3% of participants had screening scores indicating postpartum depression, while a substantial proportion exhibited mild to moderate depressive symptoms. Early screening using standardized tools demonstrated good sensitivity and specificity in identifying mothers at risk. Early screening is an effective strategy for identifying postpartum depression among high-risk mothers. Integrating routine mental health screening into maternal healthcare services can improve early detection, enable timely intervention, and enhance maternal mental health outcomes during the postpartum period.